Comparing the Effects of Loving-Kindness Meditation (LKM), Music and LKM Plus Music on Psychological Well-Being. Issue 3 (3rd April 2019) - Sorensen, Susan; Steindl, Stanley R.; Dingle, Genevieve A.; Garcia, Anthony
Abstract: Loving-kindness meditation (LKM), a meditative practice directing caring feelings toward self and others, is a popular, evidence-base approach to increasing well-being. Music listening is also a popular form of emotion regulation used to enhance well-being. This interdisciplinary study evaluated a novel intervention called Convergence—combining LKM with accompanying classical guitar music—and its effects on adults' well-being, mindfulness, compassion and self-compassion outcomes. Convergence was compared to active control groups LKM-only and Music-only regarding their relative effectiveness in improving these outcomes. Participants ( N  = 78; aged 18 to 69 years; 90% females; recruited from the general public) were assigned to either the Convergence, LKM-only, or Music-only condition. Each condition received a 2-hour workshop, involving psychoeducation, three prerecorded meditations, and group enquiry and discussion. Participants were assessed at pre-program, post-program, and 4-week follow-up. Findings revealed that Convergence, LKM-only and Music-only were equally effective interventions, producing improvements in dependent variables with small effect sizes. There was no additive effect of the components when delivered together as Convergence. Significant correlations were found between the amount of home practice, and mindfulness and self-compassion at follow-up. LKM, music listening and Convergence all provide brief, evidence-based alternatives for improving well-being. Practical and theoretical implications are provided, as well as recommendations for future research.